2018
DOI: 10.1136/postgradmedj-2017-135515
|View full text |Cite
|
Sign up to set email alerts
|

Frequency, comprehension and attitudes of physicians towards abbreviations in the medical record

Abstract: Abbreviations are common in medical records and are frequently misinterpreted. Online teaching is a valuable tool for physician education. The majority of respondents believed that misinterpreting abbreviations could negatively impact patient care, and that the use of abbreviations should be prohibited in medical records. Due to low rates of comprehension and negative attitudes towards abbreviations in medical communications, we believe their use should be discouraged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The EHR corpus was marred by irregular spelling, irregular abbreviations, typographical errors, grammatical errors, and other irregularities absent from the OMIM corpus and the Textbook corpus. Others have noted the high frequency of irregular abbreviations, spelling, grammatical, and other writing errors in the clinical notes created by physicians (68)(69)(70)(71)(72) The general approach of the writers of the OMIM corpus was brevity. OMIM writers tended to use lists of clinical concepts such as "the patient had optic disk pallor, miosis, anisocoria, and a relative afferent pupil defect."…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The EHR corpus was marred by irregular spelling, irregular abbreviations, typographical errors, grammatical errors, and other irregularities absent from the OMIM corpus and the Textbook corpus. Others have noted the high frequency of irregular abbreviations, spelling, grammatical, and other writing errors in the clinical notes created by physicians (68)(69)(70)(71)(72) The general approach of the writers of the OMIM corpus was brevity. OMIM writers tended to use lists of clinical concepts such as "the patient had optic disk pallor, miosis, anisocoria, and a relative afferent pupil defect."…”
Section: Discussionmentioning
confidence: 99%
“…The lower accuracy for recognition of signs and symptoms in the EHR corpus (physician notes) deserves further comment. One way to improve automated recognition of signs and symptoms in physician notes is to encourage them to use structured rather than unstructured documentation ( 73 ). However, given physician burnout associated with clinical documentation ( 74 ), and physician distaste for structured documentation ( 75 ), it seems unlikely that physicians will adopt structured documentation for recording signs and symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Subspecialty abbreviations are better understood by doctors working in the same field of work, 9,10,18 evidenced by a study on interpretation of ophthalmology abbreviations by Hamiel et al 19 . In this study, less than half of surveyed non‐ophthalmologists were able to correctly interpret 10% or more of ophthalmology abbreviations found in medical records, and no non‐ophthalmologists were able to interpret them all 19 …”
Section: Introductionmentioning
confidence: 56%
“…International literature has previously indicated that there is incomplete understanding of abbreviations by doctors, with doctors correctly interpreting only 37–73% of abbreviations across various specialties 14–17 . Subspecialty abbreviations are better understood by doctors working in the same field of work, 9,10,18 evidenced by a study on interpretation of ophthalmology abbreviations by Hamiel et al 19 . In this study, less than half of surveyed non‐ophthalmologists were able to correctly interpret 10% or more of ophthalmology abbreviations found in medical records, and no non‐ophthalmologists were able to interpret them all 19 …”
Section: Introductionmentioning
confidence: 99%
“…The number of abbreviations that prior methods have evaluated varies from 13 to 1116 15 – 18 , with separate models typically developed for each abbreviation. Many studies include only abbreviations that are “ambiguous” (i.e., multiple long forms for the abbreviation) 18 , although unambiguous abbreviations can be difficult even for physicians in other specialties to discern 19 , 20 . To detect abbreviations in text, prior research focuses on heuristics, such as string matching of abbreviations like “ivf,” rather than machine learning 20 – 22 .…”
Section: Introductionmentioning
confidence: 99%